Incidencia socioeconómica del plan de desarrollo estratégico municipal del cantón Bolívar período 2011-2012 - Villamar González, Víctor Fernando (2013)
The purpose of this research was to optimize the mismanagement and execution of the Strategic Development Plan in Bolívar Canton through an assessment of the socio-economic impact on the population; technical tools were applied for the correct analysis of the objectives, strategies and implementation of projects implied in the plan by the measurement of indicators. Methods were used such as SWOT analysis, impact monitoring and evaluation matrix, supplemental technical information, interviews, and socio-economic impact assessment through surveys of socio-economic indicators of the Strategic Development Plan. This contributed to the achievement of the expected results for a proper analysis of the social and economic influence, as well as the proposed corrective actions to optimize their operation and management, so the development plan acquires a positive socio-economic impact in the Bolívar Canton.